Conocimientos, actitudes y prácticas en la salud sexual y reproductiva de adolescentes y jóvenes de la ciudad de Loja. - Morocho Guadalima, José Fernando (2013)
Teenagers reach sexual maturity before they are emotionally, socially and cognitively stable. This leads to an experimentation environment, where sexual relations, promiscuity, a lack of use of contraceptive measures and the use of drugs are permanent occurrences. Seeing this problem, an investigation work has been done, which has been entitled KNOWLEGE, ATTITUDES AND PRACTICES ON SEXUAL AND REPRODUCTIVE HEALTH IN TEENAGERS AND YOUNG ADULTS FROM LOJA CITY. Its focus is to form a clear picture of the level of knowledge, attitudes and sexual health practices of teenagers and young adults in Loja City, establishing the age and genre group that is affected the most by the lack of knowledge and inappropriate attitudes. This way, it will be possible to plan strategies for permanent and continuous education in the topics of sexuality and human reproduction. This investigation work has a descriptive and observation based nature, with field research and multidisciplinary reach, using non probabilistic sampling. It was applied to one hundred and ninety-five people, with a previous testing. The retrieved data was collected using a personal survey entitled “MY SEXUALITY AND I”, which includes one hundred and forty two items grouped in three sections (sexual and reproductive health, HIV/AIDS, and condom use) and three categories: knowledge, attitudes and practices. Some surveys were used as reference, including YRHBS, DSFI, SKAT, CHIP, and two surveys carried out in Latin America. Most of the knowledge shown by the people who filled the surveys was in the “half adequate” category, same as the attitudes and practices; with the exception of those related to HIV/AIDS, where knowledge and practices were considered to be in adequate. The most affected people in the categories where eighteen years olds, as well as males. This investigation work serves as a source of data about knowledge, attitudes and practices about sexual and reproductive health of teenagers and young adults. It contributes to identify risk and protection factors for the young population of Loja City; and to the planning of high quality strategies and programs to diminish the existing problems and to promote basic sexual health habits in teenagers and young adults. Keywords: Teenagers, Young adults, sexual, reproductive, HIV, AIDS, preservative.